Immunological and Clinical Approaches in Determining Indications for Tonsillectomy: A Literature Review - Anantasya, Arum Widya; Adji, Iwan Setiawan; Megaranti, Ardhini Tyas; Ramadhani, Zerlina Norberta; Mukti, Gavin Editya; Devano, Mohammad Alifiya (Jurnal Dunia Kesmas, 2026)
The palatine tonsils play a key role in mucosal immune defense; however, chronic tonsillitis leads to structural and immunological impairment, resulting in loss of protective function and persistent infection. Current indications for tonsillectomy rely mainly on infection frequency and anatomical findings, which may be insufficient. This literature review aims to evaluate tonsillar immune dysfunction and the role of clinical parameters in establishing a more comprehensive indication for tonsillectomy. A PRISMA-based literature review of studies published between 2010 and 2025 was conducted. The findings demonstrate impaired lymphocyte maturation, reduced secretory IgA production, chronic inflammatory activity, and bacterial biofilm formation in chronic tonsillitis. Clinical parameters including the Centor score, McIsaac score, FeverPAIN score, Paradise criteria, tonsillar hypertrophy, airway obstruction such as obstructive sleep apnea, and quality-of-life assessment using the Tonsillectomy Outcome Inventory-14 (TOI-14) provide objective evaluation of disease severity and functional burden. In conclusion, tonsillectomy should be considered based on an integrated assessment of clinical, anatomical, immunological, and quality-of-life parameters to support evidence-based surgical decision-making.